The Impact Of Work Environment And Loyalty On Productivity With Organizational Commitment As A Mediating Variable In Jember's Civil Registration Office - Savitri, Nikke Indah; Sanosra, Abadi; Cahyono, Dwi (SEAN Institute, 2024)
Fluctuations in productivity over the past five years raise questions about factors influencing employee performance, including human resources, information technology, operational processes, and policies. This study investigates the impact of the work environment and employee loyalty on productivity, with organizational commitment as a mediating variable, within the Department of Population and Civil Registration in Jember Regency. Using a causal-comparative approach, primary data were collected from 103 employees through questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (SEM-PLS) via WarpPLS. The findings reveal that both the work environment and employee loyalty significantly enhance productivity, directly and indirectly, through organizational commitment. Additionally, organizational commitment significantly mediated these relationships, demonstrating its critical role. These results underscore the importance of creating a supportive and conducive work environment and fostering employee loyalty to improve overall productivity. The implications suggest that the department should focus on enhancing work conditions, providing recognition and rewards, and ensuring effective communication to boost employee commitment and productivity, contributing to the organization’s success. This research offers valuable insights for organizational management to develop strategies that enhance employee engagement and efficiency.